The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9041047
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant TP53 Mutation Confers Worse Prognosis in EGFR-Mutated Non-Small Cell Lung Cancer Patients Treated with TKIs

Abstract: Background: Non-small cell lung cancer (NSCLC) is the primary cause of cancer-related deaths worldwide. Epidermal Growth Factor Receptor (EGFR)-mutated patients usually benefit from TKIs treatment, but a significant portion show unresponsiveness due to primary resistance mechanisms. We investigated the role of TP53 mutations in predicting survival and response to EGFR-TKIs in EGFR-mutated NSCLC patients, to confirm, on an independent case series, our previous results. Methods: An independent retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 30 publications
8
51
2
Order By: Relevance
“…We found that the TP53 gene had a higher mutation rate in people younger than or equal to 65 years old, reaching 53.8%, and it was only 40% in people over 65 years old, which was consistent with the results of previous studies [32,33]. We also con rmed that TP53 mutations did not affect the prognosis of patients with LUAD, it was consistent with the result of the study by Szymanowska, A., et al [34][35][36][37][38][39]. However, other studied suggested that patients with mutations of the TP53 gene had a poor prognosis [15,32,33,40,41].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the TP53 gene had a higher mutation rate in people younger than or equal to 65 years old, reaching 53.8%, and it was only 40% in people over 65 years old, which was consistent with the results of previous studies [32,33]. We also con rmed that TP53 mutations did not affect the prognosis of patients with LUAD, it was consistent with the result of the study by Szymanowska, A., et al [34][35][36][37][38][39]. However, other studied suggested that patients with mutations of the TP53 gene had a poor prognosis [15,32,33,40,41].…”
Section: Discussionsupporting
confidence: 92%
“…Lung cancer is linked with somatic mutations in the EGFR , TP53 , KRAS , and ALK genes [ 4 , 5 ]. Concomitant TP53 mutation in EGFR -mutated NSCLC patients is associated with poor prognosis [ 6 ]. Another lung cancer feature is a high ability to invade neighboring tissues and metastasize to distant organs.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon for patients to have concurrent mutations alongside exon 20 insertions ( 21 ); therefore, we speculate that the difference in afatinib response could be owing to the presence of an additional mutation. For example, TP53 mutations are one of the most common concurrent mutations alongside exon 20 insertion ( 21 ) and is possibly associated with a lower likelihood of response to EGFR TKIs ( 22 ). Overall, these findings are particularly interesting and suggest that afatinib may provide a new therapeutic option for the particular type of mutation discussed here.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%